Zero-field nuclear magnetic resonance of chemically exchanging systems - Danila A. Barskiy (Nature Portfolio, 2019)
Zero-field nuclear magnetic resonance can identify species and collective behaviors in mixtures without applied magnetic fields. Here the authors demonstrate its use for resolving proton exchange in ammonium and for the detection of hyperpolarized pyruvic acid, an important imaging biomarker.